2015
DOI: 10.1371/journal.pone.0144519
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Triple-Transgenic Forsythia Cell Cultures as a Platform for the Efficient, Stable, and Sustainable Production of Lignans

Abstract: Sesamin is a furofuran lignan biosynthesized from the precursor lignan pinoresinol specifically in sesame seeds. This lignan is shown to exhibit anti-hypertensive activity, protect the liver from damages by ethanol and lipid oxidation, and reduce lung tumor growth. Despite rapidly elevating demand, plant sources of lignans are frequently limited because of the high cost of locating and collecting plants. Indeed, the acquisition of sesamin exclusively depends on the conventional extraction of particular Sesamum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…Subsequently, cell suspension culture lines of F . koreana were established from the calli as described previously [ 9 ] and were maintained at 22°C in Gamborg’s B-5 liquid medium supplemented with 6% sucrose and 0.05 mg l-1 2,4-D (Cell Culture Medium; CCM). All suspensions were cultured on a rotary shaker at 110 rpm in the dark and were subcultured every 2 weeks with an inoculum of 5 ml of saturated suspension cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, cell suspension culture lines of F . koreana were established from the calli as described previously [ 9 ] and were maintained at 22°C in Gamborg’s B-5 liquid medium supplemented with 6% sucrose and 0.05 mg l-1 2,4-D (Cell Culture Medium; CCM). All suspensions were cultured on a rotary shaker at 110 rpm in the dark and were subcultured every 2 weeks with an inoculum of 5 ml of saturated suspension cells.…”
Section: Methodsmentioning
confidence: 99%
“…There is a growing body of evidence for the diverse biological effects of lignans on mammals, including antioxidative, antiobesity, antitumor, antiviral activities, and the reduction of the risk of various cancers and cardiovascular diseases [ 6 8 ]. Quite recently, we also demonstrated the marked usefulness of triple-transgenic Forsythia callus suspensions as efficient, stable, and sustainable platforms for the production of a beneficial non- Forsythia lignan, sesamin [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, these effects are due to the presence of a specific class of secondary metabolites, the lignans (phenylpropane dimers originating from the phenylpropanoid pathway [ 100 ]), which bind to the human sex hormone globulin and act as hormone balancer [ 101 ]. The production of lignans is usually achieved via plant cell suspension and hairy root cultures [ 102 , 103 , 104 , 105 , 106 ]. Their production in heterologous systems is not yet a viable option, since not all the players partaking in the pathway leading to specific lignin formation are known [ 107 ].…”
Section: Valorizing Stinging Nettle For the Production Of Phenolicmentioning
confidence: 99%
“…In HR-type systems, several studies have demonstrated the feasibility of engineering lignans biosynthesis in various flax species such as L. album, L. perenne, or L. corymbulosum [57,58,67]. In cell culture systems of F. koreana, it was possible to redirect the lignan biosynthetic pathway to the accumulation of new lignan compounds not naturally produced by this plant by a metabolic engineering approach [158,159]. Although yields were very low, the transient expression of several biosynthetic genes in tobacco leaves resulted in the production of an Etoposide precursor [83].…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%